KUALITAS KINERJA WIDYAISWARA DALAM PENINGKATAN KOMPETENSI PEGAWAI NEGERI SIPIL PROVINSI SULAWESI BARAT - Nurbayani Nurbayani (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2018)
This study aims to determine the extent of the quality of the performance of the Widyaiswara in an effort to improve the potential of Civil Servants in West Sulawesi Province. This study uses a qualitative descriptive method that collects data through observation and interviews, with analysis using the theory of human resources, specifically the concept of evaluating the quality of work from Panggabean. The results of the study indicate that the quality of work of the Lecturers at the National Council for Training and Education of the Province of West Sulawesi must be improved in their abilities and positions. These are because the lecturers at the National Board of Education and Training of West Sulawesi are now only involved in training and education structurally. Only a few training and education techniques from the Widyaiswara can be involved. Activities to develop their potential can be obtained with colloquia and workshops; call of paper; multiplying working hours, and others that increase their ability and credit amount to meet standards for promotional positions.